2005
DOI: 10.1523/jneurosci.2267-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin Regulates the Cell Surface Dynamics of Synaptic GABAAReceptors

Abstract: The efficacy of fast synaptic inhibition is critically dependent on the accumulation of GABA A receptors at inhibitory synapses, a process that remains poorly understood. Here, we examined the dynamics of cell surface GABA A receptors using receptor subunits modified with N-terminal extracellular ecliptic pHluorin reporters. In hippocampal neurons, GABA A receptors incorporating pHluorin-tagged subunits were found to be clustered at synaptic sites and also expressed as diffuse extrasynaptic staining. By combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
268
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(301 citation statements)
references
References 43 publications
26
268
1
Order By: Relevance
“…pHluorin-tagged GluA2 (pH-GluA2) and γ2S (pH-γ2S) were used for the study, because these subunits are common subunits of AMPA and GABA A receptor complexes in hippocampus, respectively. Previous studies have confirmed that the pHluorin tag does not affect trafficking of these receptor subunits in neurons (15,23).…”
Section: Resultsmentioning
confidence: 78%
“…pHluorin-tagged GluA2 (pH-GluA2) and γ2S (pH-γ2S) were used for the study, because these subunits are common subunits of AMPA and GABA A receptor complexes in hippocampus, respectively. Previous studies have confirmed that the pHluorin tag does not affect trafficking of these receptor subunits in neurons (15,23).…”
Section: Resultsmentioning
confidence: 78%
“…Pharmacological treatments provided additional information on the mechanisms controlling the distribution of GABA A Rs. We tested the role of MTs, which play a crucial role in axon growth and in directional sensing mechanisms (10,20) and interact, at least indirectly, with GABA A Rs (21,22). We found that the asymmetric redistribution of the receptors was suppressed when MTs were depolymerized with nocodazole (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The results of the experiments with taxol thus do not favor the hypothesis of the interactions with a motor. The directed movements were more likely due to the receptors binding to MT ends, possibly by means of other molecular partners (21,22), and being displaced during MT polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of GABARs at synaptic sites is governed by lateral migration within the membrane, rather than insertion of newly synthesized receptors (26), where interactions with scaffolding proteins such as gephyrin stabilize postsynaptic receptors (51). Furthermore, GABAR insertion and endocytosis via AP2 adaptin occur predominantly at extrasynaptic sites, indicating that lateral diffusion and trafficking of receptors are critically important for regulating synaptic strength at GABAergic synapses (25).…”
Section: Discussionmentioning
confidence: 99%